A heat-insulating transparent polypropylene material and its preparation method and application
By introducing nano-tin oxide antimony powder and nano-seafoil fibers into the polypropylene material, the problem of transparent polypropylene material lacking thermal insulation function is solved, and the high transparency and thermal insulation properties of the material are achieved.
Patent Information
- Application Number
- CN202310520512.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-05-10
AI Technical Summary
The existing transparent polypropylene materials lack thermal insulation and thermal insulation functions, and cannot meet the application needs of high transparency and thermal insulation performance.
By introducing nano-tin oxide antimony powder into the polypropylene material, a nanofilled layer with high near-infrared absorption is formed, and nano-seafoil fibers are used to uniformly adsorb and disperse nano-tin oxide antimony to ensure the transparency and insulation effect of the material.
The high transparency and thermal insulation properties of polypropylene materials are achieved, which significantly reduces the radiation dispersion rate of heat inside the material, and meets the demand for high transparency and thermal insulation.
Smart Images

Figure BDA0004220665530000011 
Figure BDA0004220665530000071 
Figure BDA0004220665530000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a heat-insulating and heat-preserving transparent polypropylene material and a preparation method and application thereof. Background Art
[0002] Polyolefin materials are widely used in daily life due to their abundant raw materials, low price, easy processing and excellent comprehensive performance. As people's requirements for quality of life increase, polypropylene materials with high visible light transmittance have gradually become the new favorite for small household storage containers. However, common transparent polypropylene materials do not have the function of heat insulation and cannot meet the application requirements of high transparency and thermal insulation performance.
[0003] Generally speaking, the thermal insulation performance of materials is mainly achieved by absorbing infrared radiation. Ceramics or glass are mainly thermally insulated by coating a film with infrared isolation effect. Since polyolefin materials have a low melting point, it is impossible to form a film on the surface of the material by high-temperature deposition. Therefore, a new method is urgently needed to achieve the high transparency and thermal insulation performance of polyolefin materials. Summary of the invention
[0004] In order to overcome the defects of the prior art, the present invention proposes a heat-insulating and heat-preserving transparent polypropylene material and a preparation method and application thereof. The polypropylene material provided by the present invention has both high transparency and heat-insulating and heat-preserving properties.
[0005] This is achieved specifically through the following technical solutions:
[0006] A transparent heat-insulating polypropylene material, comprising the following components by weight:
[0007]
[0008]
[0009] The average particle size of the nano antimony tin oxide powder is 50-70nm.
[0010] The present invention adopts nano antimony tin oxide powder, that is, nano tin oxide (doped with Sb) to form a nano filling layer with high near infrared absorption rate in the inner layer of the material. At the same time, due to its nano scale (smaller than the wavelength of visible light 400-700nm), it does not affect the transparency of the material, so a polypropylene material with high transparency and thermal insulation effect can be realized. In addition, sepiolite fiber has adsorption and flowability, and nano antimony tin oxide can be uniformly adsorbed on the sepiolite fiber, and its flowability is used to ensure that these fibers are uniformly distributed in the entire material, thereby avoiding the agglomeration effect of nano particles, and greatly improving the thermal insulation performance of the polypropylene material.
[0011] Furthermore, the antimony oxide content in the nano antimony tin oxide powder is 4-6wt%. If the doping amount of antimony oxide is too low, the energy absorption is insufficient and the thermal insulation effect is not obvious; if the doping amount is too high, the nano agglomeration effect is enhanced and effective dispersion cannot be achieved.
[0012] Further, the aspect ratio of the nano sepiolite fiber is 5:1-20:1, and the average diameter is 1-10nm. The aspect ratio of the nano sepiolite fiber determines its adsorption and fluidity. The smaller the aspect ratio, the better the fluidity, but the weaker the adsorption capacity. The aspect ratio of the nano sepiolite fiber in the present invention is preferably 5:1-20:1 to ensure that it has better adsorption capacity and fluidity at the same time.
[0013] Furthermore, the polypropylene resin is one or more of homopolymer polypropylene, block copolymer polypropylene, and random copolymer polypropylene, and the melt index is 10-50g / 10min. The melt index test condition of polypropylene is 230°C / 2.16Kg, and the test standard is ISO 1133-1-2011. The influence of the melt index mainly has two aspects: too low will be unfavorable for the dispersion of nano antimony tin oxide, while too high melt index will easily cause bubbles in the injection molding process and fail to achieve a good thermal insulation effect.
[0014] Furthermore, the nucleating agent is a sorbitol nucleating agent. Compared with other nucleating agents, sorbitol nucleating agents can better refine the crystal nucleus and help improve transparency.
[0015] Furthermore, the sorbitol nucleating agent includes, but is not limited to, one or more of unsubstituted dibenzylidene sorbitol, (1,3,2,4-di(p-methyldibenzylidene) sorbitol, (1,3,2,4)-di(3,4-dimethyl)benzylidene sorbitol, and a condensate of n-propylbenzaldehyde and n-propyl sorbitol.
[0016] Furthermore, the heat insulating transparent polypropylene material also includes 1-5 parts of antioxidants and processing aids.
[0017] Furthermore, the antioxidant is one or more of phenolic, phosphite, divalent sulfur, and hindered amine antioxidants.
[0018] Preferably, the phenolic antioxidant is one or more of antioxidant 264, antioxidant 1010, antioxidant 1076, antioxidant SP, antioxidant 2246, antioxidant CA, antioxidant 330, Irganox1890, and antioxidant 3114; the phosphite antioxidant is one or more of antioxidant TNP, antioxidant ODP, antioxidant 168, Irganox1093, and Irganox1222; the divalent sulfur antioxidant is one or more of dilauryl thiodipropionate (DLTP) and distearate thiodipropionate (DSTP); the hindered amine antioxidant includes but is not limited to one or more of amine antioxidants such as LS-744, LS-770, GW-540, and FlamstabNOR116.
[0019] Furthermore, the processing aid is one or more of low molecular lipids, metal soaps, stearic acid complex esters, and amides.
[0020] Preferably, the low molecular lipids are one or more of solid paraffin, liquid paraffin, and low molecular polyolefin wax; the metal soaps are one or more of calcium stearate, magnesium stearate, zinc stearate, and barium stearate; the stearic acid complex esters are one or more of ethylene glycol stearate, glyceryl stearate, and pentaerythritol stearate; and the amides are one or more of erucamide, methylene bisstearamide, and N,N-ethylene bisstearamide.
[0021] Furthermore, the content of polypropylene resin in the heat insulating and heat-retaining transparent polypropylene material is not less than 80wt%.
[0022] The present invention also provides a method for preparing the above-mentioned heat insulating and heat-preserving transparent polypropylene material, comprising the following steps:
[0023] S1: according to the ratio, weigh the nano-sepiolite fiber and the nano-tin antimony oxide powder and pre-mix them to obtain a premix;
[0024] S2: the premix of step S1 and polypropylene resin, nucleating agent, antioxidant and processing aid are put into an extruder according to a proportion, melt blended and extruded into granules to obtain the heat insulating and heat-retaining transparent polypropylene material.
[0025] Furthermore, the extruder is a twin-screw extruder, the screw aspect ratio of the twin-screw extruder is 40:1, and the barrel temperature of the twin-screw extruder is 190-220° C. Sepiolite is an inorganic mineral with a decomposition temperature above 350° C. The melt extrusion temperature of the present invention is about 200° C., so the structure of the nano-sepiolite fiber will not change significantly during melt extrusion; and the sepiolite fiber is a non-rigid fiber, and its fiber length will not change significantly during the melt extrusion process.
[0026] The present invention also provides application of the heat-insulating transparent polypropylene material in preparing a transparent container.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1) The present invention introduces nano tin oxide into the polypropylene resin material and dopes it with a special rare earth element antimony, so that it has a good absorption effect in both near-infrared and far-infrared light, significantly reducing the rate at which the heat inside the material is dissipated in the form of radiation. In addition, the particle size of the antimony tin oxide is controlled to be smaller than the nanometer scale of the visible light wavelength, thereby obtaining a transparent polypropylene material with heat insulation effect without affecting the transparency of the base material.
[0029] 2) Since nano-scale antimony tin oxide particles have a large specific surface area and are easy to agglomerate, which is common in nanoparticles, they cannot fully utilize their characteristics of absorbing infrared thermal radiation. The present invention also introduces nano-sepiolite fibers with a high aspect ratio, which can adsorb nano-antimony tin oxide particles on the fiber surface, and utilize its fluidity so that during the injection molding process, the axial direction of the fiber can be oriented and distributed along the melt flow direction, fully ensuring the uniform distribution of nano-antimony tin oxide inside the material, thereby improving the thermal insulation effect. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] <Preparation of Examples and Comparative Examples>
[0032] The raw materials used in the examples and comparative examples of the present invention are all commercially available, but are not limited to these materials:
[0033] Homopolymer polypropylene resin A: melt index 50 g / 10 min, brand PP H9018, purchased from Lanzhou Petrochemical;
[0034] Homopolymer polypropylene resin B: melt index is 25 g / 10 min, brand N-Z30S, purchased from Sinopec Chemical Co., Ltd.;
[0035] Homopolymer polypropylene resin C: melt index is 10 g / 10 min, brand PP HP500N, purchased from Sinopec Chemical Co., Ltd.;
[0036] Homopolymer polypropylene resin D: melt index 3 g / 10 min, brand PP T30S, purchased from Sinopec Chemical Co., Ltd.;
[0037] Homopolymer polypropylene resin E: melt index 60 g / 10 min, grade PP H9018, purchased from China National Petroleum Corporation;
[0038] Nano-antimony tin oxide A: average particle size 70nm, antimony oxide content 4wt%, brand LM-002, purchased from Keeling Walker Company, UK;
[0039] Nano-antimony tin oxide B: average particle size 55nm, antimony oxide content 6wt%, brand LM-008, purchased from Keeling Walker Company, UK;
[0040] Nano-tin antimony oxide C: average particle size 50nm, antimony oxide content 5wt%, brand CP6C, purchased from Keeling Walker Company, UK;
[0041] Nano antimony tin oxide D: average particle size 35nm, antimony oxide content 4wt%, brand LM-010, purchased from Keeling Walker Company, UK;
[0042] Nano-antimony tin oxide E: average particle size 120nm, antimony oxide content 4wt%, brand LM-007, purchased from Keeling Walker Company, UK;
[0043] Nano antimony tin oxide F: average particle size 70nm, antimony oxide content 8wt%, brand LM-004, purchased from Keeling Walker Company, UK;
[0044] Tin oxide: average particle size of 52 nm, antimony oxide content of 0%, brand ATO, purchased from Merck Chemical, USA;
[0045] Nano sepiolite fiber A: aspect ratio of 5:1, average diameter of 1 nm, brand No. 1 sepiolite powder, purchased from Hebei Antai Hengxin;
[0046] Nano sepiolite fiber B: aspect ratio of 12:1, average diameter of 5 nm, brand No. 3 sepiolite powder, purchased from Hebei Antai Hengxin;
[0047] Nano sepiolite fiber C: aspect ratio of 20:1, average diameter of 10 nm, brand sepiolite powder No. 2, purchased from Hebei Antai Hengxin;
[0048] Nano sepiolite fiber D: aspect ratio of 2:1, average diameter of 10 nm, brand sepiolite powder No. 0, purchased from Hebei Antai Hengxin;
[0049] Nano sepiolite fiber E: aspect ratio of 100:1, average diameter of 10 nm, brand Clay 20, purchased from Tolsa Group, Spain;
[0050] Nucleating agent: sorbitol, brand NX-8000K, purchased from Milliken, USA;
[0051] Antioxidant: The main antioxidant of the antioxidant is a hindered amine, brand SONOX 1010, purchased from Shandong Sanfeng Chemical Co., Ltd.; the secondary antioxidant is a phosphate ester, brand SONOX 168, purchased from Shandong Sanfeng Chemical Co., Ltd., wherein the weight ratio of the main antioxidant to the secondary antioxidant is 1:1;
[0052] Processing aid: calcium stearate, commercially available.
[0053] The preparation methods of the embodiments of the present invention and the comparative examples are as follows:
[0054] S1: According to the ratios in Table 1 and Table 2, weigh each component, and premix the nano-sepiolite fiber and nano-tin antimony oxide powder in a high-speed mixer to obtain a premix;
[0055] S2: putting the premix of step S1 and the remaining weighed components into a twin-screw extruder for melt blending and extrusion granulation to obtain a heat insulating and heat-retaining transparent polypropylene material.
[0056] The screw length-diameter ratio of the twin-screw extruder is 40:1, the barrel temperature is 190°C, and the screw speed is 450 r / min.
[0057] <Sample Preparation>
[0058] Injection molding was adopted with an injection temperature of 200°C, a holding pressure of 100MPa, and a back pressure of 5MPa to mold square plates of 100*100*2.0mm, square plates of 200*60*2.0mm, and rectangular plastic boxes of 200*50*50mm (thickness of 2.0mm) respectively.
[0059] The term "part(s)" in this specification means "part(s) by weight" unless otherwise specified.
[0060] <Test Standard>
[0061] The polypropylene materials of the embodiments of the present invention and the comparative examples were made into square plates or plastic boxes for performance testing, and the standards were as follows:
[0062] Transmittance: Use a transmittance tester to test the transmittance of a 100*100*2.0mm square plate in the visible light range.
[0063] Absorption rate: A near-infrared spectrometer was used to test the near-infrared light absorption rate of a 100*100*2.0mm square plate at a wavelength of 1064nm.
[0064] Heat insulation effect: Pour 100ml of 80℃ distilled water into a 200*50*50mm rectangular plastic box, cover the surface of the box with a 200*60*2.0mm square plate, and use a temperature sensor to detect the temperature of the water in the box (read the temperature of the sensor every 2 hours).
[0065] Table 1. Formulations of Examples 1-9
[0066]
[0067]
[0068] Table 2. Comparative Examples 1-6 Formula
[0069]
[0070] Table 3. Performance test results of Examples 1-16
[0071]
[0072]
[0073] Table 4. Performance test results of comparative examples 1-6
[0074]
[0075] Generally, a transmittance of 80% is acceptable, and a near-infrared light absorptivity of 50% is acceptable. As can be seen from Table 3, the transmittance of the polypropylene resin material prepared by the present invention is above 80%, and the near-infrared light absorptivity is above 50%, while meeting the requirements of thermal insulation and transparency.
[0076] Combined with Table 3, compared with Examples 1, 4, and 7, Examples 10 and 11 show that the melt index of the polypropylene resin affects both the transmittance and the thermal insulation effect. If the melt index is too low, it will be detrimental to the dispersion of nano antimony tin oxide therein, while if the melt index is too high, bubbles are likely to appear during the injection molding process, and a good thermal insulation effect cannot be achieved.
[0077] Compared with Example 2, the doping amount of antimony oxide in nano-antimony tin oxide is higher. It can be seen that the nano-agglomeration effect is obvious and it cannot be effectively dispersed, affecting the transparency.
[0078] Compared with Examples 3, 6, and 9, Examples 13 and 14 show that the aspect ratio of the nano-sepiolite fiber determines its adsorption and flowability. The smaller the aspect ratio, the better the flowability, but the weaker the adsorption capacity, which affects the thermal insulation effect; the larger the aspect ratio, the lower the flowability, which in turn affects the uniform distribution of nano-tin antimony oxide in the material, reducing the visible light transmittance.
[0079] Combined with Table 4, the embodiments and comparative examples are analyzed:
[0080] Compared with Example 2, in Comparative Example 1, tin oxide is added instead of nano-tin antimony oxide, and its near-infrared light absorption rate is significantly reduced, and the thermal insulation effect in the box is not good; compared with Example 2, in Comparative Examples 2 and 3, too much or too little addition of nano-tin antimony oxide will affect the thermal insulation and transparency effects. If too much is added, the transmittance will be reduced; if too little is added, the thermal insulation effect will be affected.
[0081] Compared with Example 2, Comparative Example 4 did not add nano-sepiolite fibers, resulting in uneven distribution of nano-tin antimony oxide, which seriously affected the thermal insulation and transparency of the material.
[0082] Comparison examples 5 and 6 show that although nano-sepiolite fiber can improve the uniformity of dispersion of nano-antimony tin oxide in the material and avoid the nano-agglomeration effect, too much addition will significantly affect the transmittance, and too little addition will not have a good adsorption and dispersion effect on nano-antimony tin oxide.
[0083] Comparing Comparative Examples 7-8 with Example 2, it can be seen that the particle size of nano antimony tin oxide is too small, the nano effect is obvious, it is difficult to effectively disperse during the processing, and the actual energy absorption efficiency is reduced; the particle size is too large, the transparency and thermal insulation effect are significantly reduced.
[0084] Embodiment 15
[0085] The polypropylene material prepared in Example 2 was made into a plastic box for testing. The results showed that the transmittance of visible light (400-700nm) was 88%, the absorptivity of near-infrared light (1064nm) was 59%, and after 80°C hot water was placed in the box for 6 hours, the temperature only dropped to 43°C. It can be considered that the polypropylene material provided by the present invention can be used to prepare a transparent container with heat insulation effect.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A heat-insulating transparent polypropylene material, characterized in that: By weight, it includes the following components: The average particle size of the nano antimony tin oxide is 50-70nm; The melt index of the polypropylene resin is 10-50 g / 10 min, and the melt index test condition is 230° C. / 2.16 Kg; The antimony oxide content of the nano antimony tin oxide is 4-6wt%; The aspect ratio of the nano-sepiolite fiber is (5:1)-(20:1), and the average diameter is 1-10 nm.
2. The heat insulating transparent polypropylene material according to claim 1, characterized in that: The polypropylene resin is one or more of homopolymer polypropylene, block copolymer polypropylene and random copolymer polypropylene.
3. The heat insulating transparent polypropylene material according to claim 1, characterized in that: The nucleating agent is a sorbitol nucleating agent.
4. The heat insulating transparent polypropylene material according to claim 3, characterized in that: The sorbitol nucleating agent includes one or more of unsubstituted dibenzylidene sorbitol, (1,3,2,4-di(p-methyldibenzylidene) sorbitol, (1,3,2,4)-di(3,4-dimethyl)benzylidene sorbitol, and a condensate of n-propylbenzaldehyde and n-propyl sorbitol.
5. The heat insulating transparent polypropylene material according to claim 1, characterized in that: It also includes 1-5 parts of antioxidants and processing aids.
6. The heat insulating transparent polypropylene material according to claim 5, characterized in that: The antioxidant is one or more of phenol, phosphite, divalent sulfur, and hindered amine antioxidants; the processing aid is one or more of low molecular lipids, metal soaps, stearic acid complex esters, and amides.
7. A method for preparing the heat insulating transparent polypropylene material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: according to the ratio, weigh the nano-sepiolite fiber and the nano-tin antimony oxide powder and pre-mix them to obtain a premix; S2: the premix of step S1 and polypropylene resin, nucleating agent, antioxidant and processing aid are put into an extruder according to a proportion, melt blended and extruded into granules to obtain the heat insulating and heat-retaining transparent polypropylene material.
8. Use of the heat insulating transparent polypropylene material according to any one of claims 1 to 6 in preparing a transparent container.
Citation Information
Patent Citations
Transparent colored heat and ultraviolet insulation film and preparation method thereof
CN103435983A
Reflection thermal-insulating coating and preparation process thereof
CN106867324A